2006
DOI: 10.1007/s00432-006-0146-0
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability analysis of bilateral breast tumors suggests treatment-related origin of some contralateral malignancies

Abstract: MSI-H is detected with a noticeable frequency in bilateral but not in unilateral breast cancers. Preferable occurrence of MSI-H in second metachronous tumors from biBC patients allows to hypothesize that the development of some contralateral breast neoplasms is casually related to the adjuvant treatment of the initial malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
(28 reference statements)
0
11
1
Order By: Relevance
“…Six MSI cases were detected in ERα, D5S346, and D17S250 markers. Our results showed only low-level MSI, defined as instability at <30-40% of loci when more than 5 markers are used (Kuligina et al, 2007), suggesting that this type of MSI is an event more frequent than high-level MSI (instability at ≥30-40% of loci) in ovarian cancer (Kuligina et al, 2007). In accordance with our results, data reported by Sood et al (2001) also showed that low-level MSI is more frequent than high-level MSI in a study of 109 ovarian tumors.…”
Section: Discussioncontrasting
confidence: 58%
“…Six MSI cases were detected in ERα, D5S346, and D17S250 markers. Our results showed only low-level MSI, defined as instability at <30-40% of loci when more than 5 markers are used (Kuligina et al, 2007), suggesting that this type of MSI is an event more frequent than high-level MSI (instability at ≥30-40% of loci) in ovarian cancer (Kuligina et al, 2007). In accordance with our results, data reported by Sood et al (2001) also showed that low-level MSI is more frequent than high-level MSI in a study of 109 ovarian tumors.…”
Section: Discussioncontrasting
confidence: 58%
“…Data from the literature suggest that MSI constitutes a rare event in sporadic breast cancer (0-3%) (Adem et al, 2003;Kuligina et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent findings indicate that as many as 1 out of 10 contralateral BCs may de facto be treatment‐induced; in particular, we observed high‐level microsatellite instability (MSI‐H) in 10% of metachronous contralateral carcinomas, but not in other categories of bilateral or unilateral BC. It is not yet clear whether this mutator phenotype results from the direct therapy‐related mutagenic inactivation of mismatch repair genes, or is attributed to positive selection of preexisting MSI‐H clones 19. Furthermore, prolonged adjuvant administration of tamoxifen reduces the incidence of hormone receptor‐positive contralateral tumors, but selects in favor of receptor‐negative metachronous malignancies 20…”
Section: Discussionmentioning
confidence: 99%